2013
DOI: 10.1007/s00420-013-0847-z
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and heart rate variability as indirect markers of surgeons’ intraoperative stress

Abstract: Our results reveal that higher perceived stress in the operating room is associated with increased intraoperative HR and decreased HRV at night. Non-stressed surgeons show greater relaxation during sleep compared to their stressed colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 63 publications
7
81
0
Order By: Relevance
“…This could increase the psychological stress and anxiety, which could in turn result in altered HRV [23,24]. The only study measuring for at least 14 days postoperatively was the study by Kimura et al [19].…”
Section: Discussionmentioning
confidence: 98%
“…This could increase the psychological stress and anxiety, which could in turn result in altered HRV [23,24]. The only study measuring for at least 14 days postoperatively was the study by Kimura et al [19].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, in the same surgeon, the autonomic nervous status did not return to the baseline level for quite a while after surgery. A HRV analysis in a previous study showed that stressed surgeons during operation, in whom the magnitude of stress was measured using the State Trait Anxiety Inventory (STAI), demonstrated less relaxation during sleep compared with non-stressed surgeons (Rieger et al 2014). Out of the surgical setting, stressors were related to a higher heart rate and lower HRV during waking as well as the sleeping period (Brosschot et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased HRV has been observed in individuals with increased psychological stress levels (Lee and Theus, 2012; Rieger et al, 2013; Suh et al, 2013) and has been proposed as a link between psychosocial risk and workplace stress in the development of metabolic and CVD (Thayer et al, 2010). Police officers may be at increased risk for decreased HRV due to their constant exposure to several occupational stressors (Covey et al, 2013; Fekedulegn et al, 2012; Miller, 2006; Violanti, 2011).…”
mentioning
confidence: 99%